Pharmacology Examination and Board Review - Trevor, Anthony J. ; Katzung, Bertram G. and Masters, Susan B. (New York Mcgraw-Hill, 2010)
Focuses on the clinical use and pharmacology of drug categories. This title includes learning aids such as: short discussion of the major concepts that underlie basic principles or drug groups; explanatory figures and tables; review questions followed by answers and explanations; and, more.
Include Index
Keywords: Pharmacology